ANALYSIS OF THE EFFECT OF CORPORATE GOVERNANCE ON COMPANY VALUE THROUGH THE ROLE OF FINANCIAL PERFORMANCE AS AN INTERVENING VARIABLE - Safitry, Syndy; Mutia, Agustina; Nengsih, Titin Agustin; Rafidah, Rafidah; Martaliah, Nurfitri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the effect of corporate governance, consisting of institutional ownership, audit committee size, independent board of commissioners, and board of directors size, on company value, namely price to book value, and to examine whether financial performance, namely return on assets, can mediate the effect of corporate governance on price to book value in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach with purposive sampling, resulting in 44 sample companies during the 2020-2024 period, with a total of 220 observations. The results show that corporate governance does not have a significant effect on financial performance. Only return on assets, institutional ownership, and independent board of commissioners have a significant direct effect on company value. However, the size of the audit committee and the size of the board of directors do not affect company value. Financial performance is also not proven to be able to mediate the influence of corporate governance on company value.